Simulation of effects of calf weaning weights on subsequent productivity - Upton, M. (International Livestock Centre for Africa, 1985)
Presents preliminary results of simulating consequences of improving calf weaning weights, by supplementary feeding or other means, on their productivity in terms of reduced mortality and increases in offtake, prices, energy value, and calving rate. Compares these with typical values in the Borana system of pastoral production in Ethiopia.